2018
DOI: 10.1002/eat.22920
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of the compuLsive Exercise Activity TheraPy (LEAP): A new approach to compulsive exercise in anorexia nervosa

Abstract: CBT-AN and LEAP added to CBT-AN resulted in improved attitudes and beliefs toward exercise and general improvements in BMI and ED psychopathology in people with AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 18 publications
4
79
0
1
Order By: Relevance
“…The present study was nested within a randomized controlled trial (RCT) . 78 adults (4 males) with AN were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…The present study was nested within a randomized controlled trial (RCT) . 78 adults (4 males) with AN were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the LEAP approach [38], our new intervention integrates elements of exercise-based therapy in a CBT approach. Exercise-based interventions may induce faster behavioral changes than CBT alone through their experiential and emotion-activating nature [75,76].…”
Section: Bmi (Itt)mentioning
confidence: 99%
“…Most of these studies are characterized by methodological shortcomings like small sample size or lack of randomization. However, Hay et al [38] recently conducted a multicenter randomized controlled trial (RCT) in an outpatient setting. They evaluated their new cognitive-behavioral therapy (CBT)-based treatment approach called compuLsive Exercise Activity theraPy (LEAP).…”
Section: Introductionmentioning
confidence: 99%
“…Men who had participated in an earlier Eating Disorder Treatment Experience survey conducted by an author (P.H.) at Western Sydney University (Hay et al, 2018) and indicated an intention to participate in this research were also invited. Participants fulfilling the selection criteria, that is, who were 18 years and older and had been diagnosed and treated for an ED, were recruited into this study.…”
Section: Procedures and Participantsmentioning
confidence: 99%